THE GREEN MOVEMENT OF SUSTAINABILITY: A CASE OF IKEA IN INDIA - Longani, Kirti Dang; Sharma, Preeti (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2024)
This research examines IKEA's sustainability movement and its impact on customer behavior. As a global leader in furniture retail, IKEA has embarked on a transformative journey to minimize its environmental footprint and promote responsible consumption practices. By integrating renewable energy, sustainable sourcing, and eco-friendly product lines, IKEA has positioned itself as a pioneer in corporate sustainability. The growing environmental concerns and increasing demand for sustainable business practices have compelled corporations to reassess their strategies. However, the extent to which corporate sustainability efforts influence consumer behavior remains a critical question. This research seeks to address this gap by evaluating the impact of IKEA’s sustainability strategies on customer behavior, particularly in terms of eco-conscious decision-making and brand loyalty. Adopting a mixed-methods approach, the study combines qualitative analysis of IKEA’s sustainability reports and initiatives with quantitative customer surveys. The theoretical foundation is rooted in the Triple Bottom Line framework, emphasizing the balance between economic, social, and environmental sustainability. IKEA’s commitment to 100% renewable energy, ethical material sourcing, and the introduction of recycled and energy-efficient products exemplifies its alignment with this framework. The findings reveal that IKEA’s sustainability initiatives empower customers to make environmentally conscious decisions and enhance brand loyalty through educational campaigns and eco-conscious product offerings. This research underscores the vital role of sustainability in shaping modern consumer behavior and driving corporate success, providing insights for corporations seeking to integrate sustainability into their business models while fostering long-term customer relationships.